Meta-Analysis the Effect of Obesity and Stress on Menstrual Cycle Disorder - Annarahayu, Lutfi; Dewi, Yulia Lanti Retno; Adriyani, Rita Benya (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: There are many factors that influence menstrual patterns to become irregular, including stress and obesity. Menstrual cycle irregularities can have a serious impact on women's health, which will affect the metabolic, fertility, sexual and reproductive systems. This study aims to analyze the influence of obesity and stress on menstrual cycle disorders with a meta-analysis study. Subjects and Method: This study is a systematic study and meta-analysis, with the following PICO, Population= women of childbearing age. Intervention= obesity and stress. Comparison = not obese and not stressed. Outcome = disruption of the menstrual cycle. The articles used in this study were obtained from several databases, including PubMed, ScienceDirect and Google Scholar. The keywords used are